The Awareness and Compliance Analysis Taxpayer Identification Number - Jajang Suherman (Ilomata International Journal of Tax and Accounting, 2020)
This article aims to determine the awareness and compliance of the taxpayer Identification number (NPWP). This article also discusses obstacles in obtaining the NPWP ownership. The research was conducted using qualitative descriptive research methods. To obtain the data, researchers observe, document studies and interviews to informant, the officers and staff of STIMLOG. Based on the results of the research, NPWP ownership has not been done effectively. Some obstacles encountered, that is for the employees do not remain to think that not always work in STIMLOG, so that ownership of NPWP is less concerned. The recommendations given to solve such problems need to involve the Tax Office, Foundation, STIMLOG, and need to be socialized both to the permanent officer and the permanent employees in order to have a NPWP.